The Effect of Endorphin Massage towards Decreasing Low Back Pain In Third Trimester Pregnant Women - Ivana Argo Cahyani; Sri Winarsih; Arfiana Arfiana (Poltekkes Kemenkes Semarang, 2020)
Background: Pregnancy becomes a meaningful experience with all the changes both physically and psychologically. One of the changes is discomfort that occurs in the third trimester is lower back pain. Lower back pain can cause disruption of daily physical activity. Endorphin massage can be one of the measures to reduce pain in third trimester pregnant women because it releases endorphins from light massage and positive affirmations from the husband.Methods: This research was conducted in the working area of Pare Public Health Center Temanggung District. The methods used Quasi Experimental with Non-Equivalent Control Group Design. The population of this study were all third-trimester pregnant women with a gestational age of 36 weeks, its about 46 people. The tool used the data collection an observation sheet on the scale of Mankoski pain. Data analysis used Wilcoxon test.Result: The results of the study used Wilcoxon test items, namely p value of endorphin massage group of 0,000 with a value of Z 3.787 and the control group p value of 0.025 with a value of Z 2.235. This showed that both groups were equally influential, but the endorphins group had a stronger influence compared to the control group.Conclusion: Endorphin massage had an effect on reduced lower back pain in the third trimester of pregnant women. Endorphin massage contain mild massage and positive affirmations from husband that stimulated the emergence of endorphin so reduce pain sensation roomates. It was expected that endorphin massage can be applied by pregnant women and husband or families as one method of decreasing low back pain because it helped empower husband / families to improve the welfare of pregnant woman.